Use of a Simple Clinical Tool for Airway Assessment to Predict Adverse Pregnancy Outcomes - Trudell, Amanda S.; Louis, Judette M.; Tuuli, Methodius G.; Caughey, Aaron B.; Odibo, Anthony O.; Cahill, Alison G. (American Journal of Perinatology, 2015)
Objective Obstructive sleep apnea (OSA) is a risk factor for adverse perinatal outcomes. We aimed to test the hypothesis that maternal Mallampati class (MC), as a marker for OSA, is associated with adverse perinatal outcomes.Study Design We performed a retrospective secondary analysis of a prospective cohort of term births (≥ 37 weeks). Fetal anomalies and aneuploidy were excluded. Primary outcome was small for gestational age (SGA). Secondary outcomes included preeclampsia, neonatal cord arterial blood gas pH < 7.10 and < 7.05, base excess <  − 8 and <  − 12 mEq/L. Outcomes were compared between mothers with low MC airways and high MC airways using logistic regression.Results A total of 1,823 women met the inclusion criteria. No significant differences were found in the risk of SGA (adjusted odds ratio [aOR] 0.9, 95% confidence interval [CI] 0.6–1.2), preeclampsia (aOR 1.2, 95% CI 0.8–1.9) or neonatal acidemia (aOR 0.8, 95% CI 0.3–2.0), between high and low MC.Conclusion High MC is not associated with adverse perinatal outcomes.
Keywords: Mallampati; obstructive sleep apnea; OSA; small for gestational age; sleep disordered breathing